2015
DOI: 10.1140/epjc/s10052-015-3608-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of interacting quintessence

Abstract: In this paper, we investigate coupled quintessence with scaling potential assuming specific forms of the coupling as A namely, αρ m , βρ φ and σ (ρ m +ρ φ ), and present phase space analysis for three different interacting models. We focus on the attractor solutions that can give rise to late time acceleration with DE / DM of order unity in order to alleviate the coincidence problem.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 85 publications
0
50
2
Order By: Relevance
“…This, as we are going to demonstrate, when done in an appropriate way, this leads naturally to a matter-dominated regime and at the same time will make the scalar field energy density dominate again at later time, closer to the recent epoch, triggering the transition from matter domination to the current accelerated regime. This approach is very much similar to the recent studies on dark matterdark energy interactions [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71]. This type of approach, in which interactions in the dark sector are assumed, has many appealing properties like, for example, providing a way of explaining the coincidence problem or at least alleviating it (for a thorough description of the properties of these dark sector interacting models, see, e.g., the review papers Refs.…”
Section: Introductionmentioning
confidence: 62%
“…This, as we are going to demonstrate, when done in an appropriate way, this leads naturally to a matter-dominated regime and at the same time will make the scalar field energy density dominate again at later time, closer to the recent epoch, triggering the transition from matter domination to the current accelerated regime. This approach is very much similar to the recent studies on dark matterdark energy interactions [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71]. This type of approach, in which interactions in the dark sector are assumed, has many appealing properties like, for example, providing a way of explaining the coincidence problem or at least alleviating it (for a thorough description of the properties of these dark sector interacting models, see, e.g., the review papers Refs.…”
Section: Introductionmentioning
confidence: 62%
“…(vi) In [355] the interaction was taken in the form Q = αρ c , Q = βρ d , and also Q = σ(ρ c +ρ d ). In all three instances no baryonic matter is considered and ω d > −1.…”
Section: More Forms Of the Interaction Kernels From Phenomenologymentioning
confidence: 99%
“…The only requirement is that the coupling constant must be very small, an indication that, observationally, the model does not differ significantly from the concordance model while it retains all the conceptual advantages of a field description. Other studies on the dynamics of coupled quintessence can be referred to, for example [355,230] …”
Section: Example II If We Choosementioning
confidence: 99%
“…It has been found that the presence of an interaction in the dark sector could successfully reconcile the long lasting cosmic coincidence problem [3,4,5,6,7]. Following this, a number of investigations in the context of interacting DE -DM models were performed by many investigators [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43] (also see two review articles in this direction [44,45]). An interesting outcome from the interaction is that, it could naturally explain the phantom dark energy equation-ofstate [46,47,48,49].…”
Section: Introductionmentioning
confidence: 99%